(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
It is important for everyone to know the rules of communication and to develop the skills and abilities to establish it. Communication is a multifaceted process of developing bonds between people arising from the needs of joint activity. includes the exchange of information between In this, the communicative aspect of the relationship is taken into account. When entering into a relationship, people first turn to language.